2013
DOI: 10.1155/2013/130582
|View full text |Cite
|
Sign up to set email alerts
|

Ultrasonic, Molecular and Mechanical Testing Diagnostics in Natural Fibre Reinforced, Polymer-Stabilized Earth Blocks

Abstract: The aim of this research study was to evaluate the influence of utilising natural polymers as a form of soil stabilization, in order to assess their potential for use in building applications. Mixtures were stabilized with a natural polymer (alginate) and reinforced with wool fibres in order to improve the overall compressive and flexural strength of a series of composite materials. Ultrasonic pulse velocity (UPV) and mechanical strength testing techniques were then used to measure the porous properties of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
14
1
6

Year Published

2016
2016
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 35 publications
(24 citation statements)
references
References 23 publications
3
14
1
6
Order By: Relevance
“…However, specimen PR22W offered the greatest increase in strength (an increase of 123% compared to the control mix) of all the specimens studied. Overall the range of values for soil U and V are comparable to the flexural results achieved by Galán-Marín et al (2013), however this study additionally demonstrated the level of flexural strength increases compared to control samples. Interestingly, in the case of the dosage study, as shown in Figure 6, increasing the dosage of alginate added to the soil mix did not significantly improve the flexural strength of the blocks.…”
Section: Flexural Strengthsupporting
confidence: 79%
See 4 more Smart Citations
“…However, specimen PR22W offered the greatest increase in strength (an increase of 123% compared to the control mix) of all the specimens studied. Overall the range of values for soil U and V are comparable to the flexural results achieved by Galán-Marín et al (2013), however this study additionally demonstrated the level of flexural strength increases compared to control samples. Interestingly, in the case of the dosage study, as shown in Figure 6, increasing the dosage of alginate added to the soil mix did not significantly improve the flexural strength of the blocks.…”
Section: Flexural Strengthsupporting
confidence: 79%
“…Indeed the final compressive strength values achieved by Galán-Marín et al (2013), even for the control specimens, are greater than those observed in this study suggesting that differences in the production process, particularly in the compaction technique should be taken into account. The unconfined compressive strength results are also lower than the typical results reported for cement stabilised earth blocks depending on the cement content and product techniques used.…”
Section: Fig 7 Compressive Strengthcontrasting
confidence: 72%
See 3 more Smart Citations